Debris Flow Modeling Using FLO-2D for Hazard Identification in the Rio Seco Creek - Castillo S, Juan (2024)
Debris flows are one of the processes of mass movements that are generated by heavy rains and are activated in the upper parts of the basins. The application case of the present research carried out in the Rio Seco stream in the district of San Bartolomé, located in the Province of Huarochirí, Department of Lima seeks to recreate a debris flow event that occurred on February 2, 2017 as a result of the climatic phenomenon in the Lima Andes. Likewise, it seeks to identify the areas of debris flow threats for different return periods Tr = 100 and Tr = 500 years. For this investigation, the mathematical model is applied using the FLO-2D software, which will process topographic data, rheological properties of the debris fluid and liquid hydrographs in different return periods. Finally, processing the data, results such as flow depth, maximum flow velocities of possible deposition zones, sediment concentration and impact force are obtained. This article is focused on comparing the debris flow and its depth with a real event adjusted with watermark control points. From the simulated results, debris flows were obtained with return periods of Tr = 100 years and Tr = 500 years, flows of 0.4 and 0.5 m3/s, tie rods with flow heights of 1.80 m and 1.90 m, respectively. Additionally, the preliminary threat map was prepared to identify vulnerable areas.